The Mirror Stares Back - Hollensteiner, Shadi (Satura, 2026)
The Mirror Stares Back delves into the psychology of body dysmorphia, capturing the often painful relationship between self-perception and physical appearance. The poem unfolds as a fragmented dialogue with the mirror, which becomes both witness and tormentor. Through paradoxical imagery the speaker expresses the confusion, shame, and yearning that characterize the dysmorphic experience.